THE EFFECT OF WORKLOAD ON TURNOVER INTENTION THROUGH JOB SATISFACTION AT FASTFOOD X IN THE CITY OF MEDAN - Asri Melya Br. Tarigan; Maya Syaula; Rizal Ahmad (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
This study aims to determine the effect of Workload through Job Satisfaction on Turnover Intention at Fastfood X in Medan City. This type of research is an associative research with a quantitative approach. The data analysis technique uses a structural equation model (SEM) with the Smart PLS analysis tool version 3.0. The sample from this researcher is 80 employees of Fastfood X in Medan City. The data collection technique used in this study is a questionnaire. The results of the study showed that workload had a positive and significant effect on job satisfaction, but did not have a direct effect on turnover. Conversely, job satisfaction has a significant effect on turnover, and it was even found that job satisfaction can be a significant mediator in the relationship between workload and turnover. These findings confirm the importance of organizational management to pay attention to the distribution of workloads and factors that affect job satisfaction in order to control turnover rates.